Long-term safety and efficacy of emtricitabine and tenofovir alafenamide vs emtricitabine and tenofovir disoproxil fumarate for HIV-1 pre-exposure prophylaxis: week 96 results from a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 7 (July 2021) - Ogbuagu, Onyema; Ruane, Peter J; Podzamczer, Daniel; Salazar, Laura C; Henry, Keith; Asmuth, David M; Wohl, David; Gilson, Richard; Shao, Yongwu; Ebrahimi, Ramin; Cox, Stephanie; Kintu, Alexander; et al.
Summary: Background: In DISCOVER, a multinational, randomised controlled trial, emtricitabine and tenofovir alafenamide compared with emtricitabine and tenofovir disoproxil fumarate showed non-inferior efficacy for HIV prevention and improved bone mineral density and renal safety biomarkers at week 48. We report outcomes analysed after all participants had completed 96 weeks of follow-up. Methods: This study is an ongoing, randomised, double-blind, multicentre, active-controlled, phase 3, non-inferiority trial done at 94 community, public health, and hospital-associated clinics located in Europe and North America. Adult cisgender men and transgender women who have sex with men, both with a high risk of acquiring HIV as determined by self-reported sexual behaviour or recent sexually transmitted infections, were randomly assigned (1:1) to receive either emtricitabine and tenofovir alafenamide (200/25 mg) tablets daily, with matched placebo tablets (emtricitabine and tenofovir alafenamide group), or emtricitabine and tenofovir disoproxil fumarate (200/300 mg) tablets daily, with matched placebo tablets (emtricitabine and tenofovir disoproxil fumarate group). The primary efficacy outcome was incident HIV infection. Incidence of HIV-1 infection per 100 person-years was assessed when the last participant had completed 96 weeks of follow-up. This trial is registered with ClinicalTrials.gov, number NCT02842086 . Findings: Between Sept 13, 2016, and June 30, 2017, 5387 participants were randomly assigned to receive emtricitabine and tenofovir alafenamide (n=2694) or emtricitabine and tenofovir disoproxil fumarate (n=2693), contributing 10 081 person-years of follow-up. At 96 weeks of follow-up, there were eight HIV infections in participants who had received emtricitabine and tenofovir alafenamide (0·16 infections per 100 person-years [95% CI 0·07–0·31]) and 15 in participants who had received emtricitabine and tenofovir disoproxil fumarate (0·30 infections per 100 person-years [0·17–0·49]). Emtricitabine and tenofovir alafenamide maintained its non-inferiority to emtricitabine and tenofovir disoproxil fumarate for HIV prevention (IRR 0·54 [95% CI 0·23–1·26]). Approximately 78–82% of participants reported taking study medication more than 95% of the time across all study visits. Rates of sexually transmitted infections remained high and similar across groups (21 cases per 100 person-years for rectal gonorrhoea and 28 cases per 100 person-years for rectal chlamydia). Emtricitabine and tenofovir alafenamide continued to show superiority over emtricitabine and tenofovir disoproxil fumarate in all but one of the six prespecified bone mineral density and renal biomarkers. There was more weight gain among participants who had received emtricitabine and tenofovir alafenamide (median weight gain 1·7 kg vs 0·5 kg, p<0·0001). Interpretation: Emtricitabine and tenofovir alafenamide is safe and effective for longer-term pre-exposure prophylaxis in cisgender men and transgender women who have sex with men. Funding: Gilead Sciences.